2012
DOI: 10.1111/pin.12005
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic lymphoma of the stomach in an HIV‐negative patient

Abstract: Plasmablastic lymphoma (PBL) is a rare B-cell neoplasm with an aggressive clinical behavior that predominantly occurs in the oral cavity of human immunodeficiency virus (HIV)-positive patients. However, it has recently been recognized that PBLs can also affect individuals without HIV infection, and suggested that these neoplasms show different clinicopathological characteristics between HIV-positive and -negative patients. Herein we describe a case of gastric PBL in a female HIV-negative patient. The tumor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…However, CD10 positivity indicated that the tumor may have stemmed from the germinal center, which is a common occurrence in PBL ( 1 ). Identification of the M protein appears to be unusual in patients with PBL, whereas monoclonal serum gammopathy has been observed in certain cases ( 12 , 13 ). IgM expression has been reported in a small minority of PBL cases, indicating that the M protein is not a strict discriminator ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, CD10 positivity indicated that the tumor may have stemmed from the germinal center, which is a common occurrence in PBL ( 1 ). Identification of the M protein appears to be unusual in patients with PBL, whereas monoclonal serum gammopathy has been observed in certain cases ( 12 , 13 ). IgM expression has been reported in a small minority of PBL cases, indicating that the M protein is not a strict discriminator ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 92%
“…Over one-third of all PBL cases were first noted at extraoral locations, predominantly within the gastrointestinal tract. According to the relevant literature, the HIVnegative patients can have PBL in the stomach, small bowel, and colon 6,9,10,13,14 . PBL of the small intestine is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmablastic lymphoma (PBL), a rare subtype of diffuse large B cell lymphoma, usually occurs in the patients with HIV infection and is primarily found in the oral cavity [1][2][3][4] . There are also reported cases of PBL in the immunocompetent individuals involving the cervical lymph nodes, stomach, lungs, cavity, small and large bowel, and liver [5][6][7][8][9][10][11][12][13][14][15] . This rare lymphoproliferative disorder is characterized by its plasmablastic morphology and immunohistochemical panel.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmablastic lymphoma is a rare and aggressive B-cell lymphoma firstly described in 1997 by Delecluse et al in the oral cavity of the immunocompromised patients [8]. In recent years, cases have been reported in HIV-negative patients, observed in the nasopharynx, maxillary sinus, orbita, skin, lung, gastrointestinal tract, soft tissue, anus, vulva, and mediastinum [1][2][3][4][5][6][9][10][11]. HIV positivity is seen in 90% of the oral PBL cases, whereas the HIV positivity in non-oral PBL cases is less prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmablastic lymphoma (PBL) is a rare and aggressive B-cell lymphoproliferative disorder [1,2,3]. It is characterized by the diffuse proliferation of large neoplastic cells mainly resembling immunoblasts with an immunophenotype of plasma cells [1,4,5].…”
Section: Introductonmentioning
confidence: 99%